2014
DOI: 10.1007/978-3-319-04981-6_38
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Vasospasm Related to Acute Subarachnoid Hemorrhage from Ruptured Aneurysms

Abstract: In the first 2 weeks after subarachnoid hemorrhage caused by a ruptured aneurysm, 30-35 % of surviving patients treated with conservative nonoperative therapy experience rebleeding. This is fatal in 60-90 % of cases and leads to significant disability in 17-20 % of cases. A major factor for this poor outcome is thought to be the vasospasm that occurs in up to 38.7 % by the third day, 46.3 % by the ninth day, and eventually in up to 70 % of patients. Endovascular treatment of aneurysms associated with acute sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The use of endovascular techniques in subarachnoid hemorrhage resulted in 85% of patients without significant disability, and <2% had a procedure related fatality. [ 46 ] Although no control group was used, this case series demonstrates good results from endovascular techniques. There were no primary studies found meeting the study criteria discussing endovascular techniques like thrombectomy in LMIC.…”
Section: Resultsmentioning
confidence: 88%
“…The use of endovascular techniques in subarachnoid hemorrhage resulted in 85% of patients without significant disability, and <2% had a procedure related fatality. [ 46 ] Although no control group was used, this case series demonstrates good results from endovascular techniques. There were no primary studies found meeting the study criteria discussing endovascular techniques like thrombectomy in LMIC.…”
Section: Resultsmentioning
confidence: 88%
“…Cerebral vasospasm frequently appears between the third and ninth days after an SAH episode ( 13 , 14 ). The underlying pathophysiological mechanisms of vasospasm and rebleeding may include increased intracranial pressure, cerebral herniation, development of acute occlusive hydrocephalus, and stroke ( 15 , 16 ). In our patient, preoperative head CT reported hydrocephalus, although neither aneurysmal rebleeding nor vasospasm occurred during her hospital stay.…”
Section: Discussionmentioning
confidence: 99%